2021
DOI: 10.3390/mi12020178
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Frequency Stabilization Approach for Mass Detection in Nonlinear Mechanically Coupled Resonant Sensors

Abstract: Frequency stabilization can overcome the dependence of resonance frequency on amplitude in nonlinear microelectromechanical systems, which is potentially useful in nonlinear mass sensor. In this paper, the physical conditions for frequency stabilization are presented theoretically, and the influence of system parameters on frequency stabilization is analyzed. Firstly, a nonlinear mechanically coupled resonant structure is designed with a nonlinear force composed of a pair of bias voltages and an alternating cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…This section discusses the nonlinear behaviour of the weakly coupled system. Continuous analyses using the shooting technique [38] are conducted to verify the effect of the different physical parameters. The referred parameters are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This section discusses the nonlinear behaviour of the weakly coupled system. Continuous analyses using the shooting technique [38] are conducted to verify the effect of the different physical parameters. The referred parameters are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…1, the multi-sensing scheme comprises a weakly coupled resonator, including cantilever and bridge resonators, mechanically coupled by a thin beam. The coupling strength could be controlled by changing the coupling position, the moment of inertia, and the coupling beam's length [38]. The detailed geometric parameters and physical properties of the coupled resonator system, considered to be fabricated from silicon, are listed in Table 1.…”
Section: Structure Description and Modelmentioning
confidence: 99%
“…They are also characterized by their output frequency and have outstanding anti-interference performance. They are widely used in measuring mass, acceleration, pressure, and so on [ 1 , 2 , 3 ]. Micromechanical resonant sensors must satisfy the whole system phase and amplitude balance condition [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In system dynamics analysis, the microresonator is equivalent to a second-order linear system [ 8 ]. However, it is reported that the microresonator is no longer equivalent to a second-order system under large amplitude vibration and behaves as a nonlinear higher-order oscillator [ 2 , 9 , 10 ]. The numerical modeling of the microresonator is not scientific enough and does not combine with the actual manufacturing size [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Micro-and nanomechanical resonators have been shown to be ultra sensitive for charge, force and mass measurements in the nonlinear regime [1][2][3][4][5][6]. However, the high sensitivity also renders the resonators susceptible to environmental fluctuations such as thermal noise [7][8][9] or molecular motion [10,11], thereby limiting their applications.…”
mentioning
confidence: 99%